The Effect of Personality Traits and Stress on Life Satisfaction in Medical Student of Sebelas Maret University - Kusprasetyo, Wahyu Tri; ., Maryani; Probandari, Ari Natalia (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Introduction: Higher life satisfaction in medical students produce health services were better in the future. One of the determining factors in life satisfaction is a personality traits. Extrovert and introvert personality can be used as consideration in choosing a policy approach to the education system in favor of life satisfaction. Also, stress in the medical education is very common. The high stress causes a decrease in academic performance and life satisfaction. The level of life satisfaction is one indicator of success in an educational institution. This study aimed to determine the effect of personality type and stress to the level of life satisfaction FK UNS Physician Education students. Methods: This research was using descriptive analytic cross-sectional approach. The study was conducted at the Faculty of Medicine UNS. Respondents were students FK UNS from 2013 to 2015. A sample of 260 students selected using stratified random sampling based on year entrance and selected according to the student identification numbers. Measuring instruments were Perceived Stress Scale (PSS), Eysenck Personality Inventory (EPI) and the Satisfaction With Life Scale (SWLS). Students were gathered in a room then got explanation and welcomed to fill out the questionnaire independently. Furthermore, the data was performed normality test and then analyzed by Pearson correlation test, followed by multiple linear regression analysis (Î± = 0,05). Results: Pearson correlation test results (0.139) show there is a very weak positive correlation between extrovert personality traits with a level of life satisfaction (p = 0.025). While there is a strong (-0.656) negative relationship between stress and the life satisfaction (p < 0.00). There is no multicollinearity relationship between these variables. Conclusions: Stress has a strong negative correlation to life satisfaction after personality traitâs variable has been controlled Keywords: Stress, Personality Traits, Life Satisfaction, Medical Education